Prospective investigation on the transfer of Ara h 2, the most potent peanut allergen, in human breast milk. Issue 4 (27th May 2016) - Schocker, Frauke; Baumert, Joseph; Kull, Skadi; Petersen, Arnd; Becker, Wolf‐Meinhard; Jappe, Uta
Abstract: Background: Peanut allergy is one of the most severe food allergies. Whether breastfeeding induces tolerance to peanuts or on the contrary, pre‐disposes at risk‐babies to occult allergic sensitization to peanuts is still a matter of discussion. We sought to investigate the transfer of the most potent peanut allergen Ara h 2 into human breast milk in a German breast milk study and to shed light on the time kinetics of Ara h 2 appearance. Methods: We recruited 32 lactating, non‐peanut‐allergic women and collected breast milk samples at different time points after consumption of 100 g dry roasted peanuts. Breast milk samples were investigated for Ara h 2 with different immunological methods: by 2D immunoblotting with a patient's serum, by affinity enrichment using a monoclonal antibody against Ara h 2 followed by LC‐MS/MS‐based detection and by a competitive inhibition ELISA for the detection of Ara h 2 and its digestion‐resistant peptides (DRP‐Ara h 2). Results: In a qualitative analysis, Ara h 2 could be identified in a breast milk sample by 2D immunoblot by means of a patient's serum and furthermore by immunoaffinity enrichment followed by LC‐MS/MS analysis. In a semi‐quantitative analysis, Ara h 2 and its digestion‐resistant peptides were detected in the breast milk of 9 of 32 subjects. Evidence suggests that Ara h 2 is excreted individually either rapidly (after 1, 2, 3 or 4 h) or delayed (after 8 or 12 h) and in different concentrations. Conclusions: Time and concentration of secreted Ara h 2 in breast milk appears to be individually regulated. The identification of Ara h 2 in breast milk is the prerequisite for the investigation of its sensitizing or tolerogenic properties. Abstract :